2010
DOI: 10.2967/jnumed.109.071340
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression of Tenascin-C After Myocardial Ischemia and Reperfusion: Assessment by 125I-Anti–Tenascin-C Antibody Imaging

Abstract: Tenascin-C, an extracellular matrix glycoprotein, appears only in the early stages of embryonic development. It is not normally expressed in the adult heart but does reappear transiently in distinct areas in association with active tissue remodeling. The aim of this study was to explore serial changes in the expression of tenascin-C after myocardial ischemia and reperfusion, using 125 I-labeled anti-tenascin-C antibody ( 125 I-TNC-Ab) in a rat model of acute ischemia and reperfusion. Methods: The left coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…For instance, it is dynamically expressed following hepatic or myocardial ischemia/reperfusion injury424344. Dysregulation of this glycoprotein was also monitored after cerebral ischemia4546.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is dynamically expressed following hepatic or myocardial ischemia/reperfusion injury424344. Dysregulation of this glycoprotein was also monitored after cerebral ischemia4546.…”
Section: Discussionmentioning
confidence: 99%
“…We found an increased tenascin (TNC) mRNA expression in both occlusion and ablation. Tenascin is sparsely detected in the normal adult myocardium, but reappears when the heart remodels its structure in response to pathologic insults, such as acute MI (Willems et al, 1996; Imanaka-Yoshida et al, 2001; Sato et al, 2006; Odaka et al, 2008), myocarditis (Imanaka-Yoshida et al, 2002; Sato et al, 2002; Morimoto et al, 2005), hibernation (Frangogiannis et al, 2002), ischemia-reperfusion (Taki et al, 2010), hypertensive cardiac fibrosis (Nishioka et al, 2007), chronic cardiac rejection (Franz et al, 2010), and some cases of dilated cardiomyopathy (DCM) (Tamura et al, 1996; Tsukada et al, 2009) closely associated with inflammation. Several studies suggest that TNC could help tissue reconstruction of the edge of the residual myocardium as a de-adhesion protein.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of antitenascin C monocolonal antibody fragment labeled with 125 I has been evaluated in rat MI models at multiple time points. Tracer uptake in the 20-minute ischemia model peaked at day 3 and declined over time with faint uptake seen at day 7 74 and suggested that probes such as those directed against tenascin may be used to monitor cardiac repair process, the extent of which depends on the severity of tissue damage. To reduce half-life and increase resolution, 111 In-single-chain antitenascin C fragment was produced, and increased uptake in the infarct was demonstrated.…”
Section: Imaging Matricellular Proteinsmentioning
confidence: 99%